Hardware Acceleration of Aggregate Signature Generation and Authentication by BLS Signature over BLS12-381 curve - Masada, Kaoru; Nakayama, Ryohei; Ikeda, Makoto (Proceedings for IEEE COOL Chips (Online), 2022)
BLS signature is a digital signature scheme computed over elliptic curves, and it has been attracting attention with its interesting function that signatures can be aggregated. We will introduce our progress of designing two ASIC architectures to accelerate the complex computations of generating and verifying signatures respectively. The computations include mapping to elliptic curves and pairing. An important subject of our work is to adopt a relatively new curve called BLS12-381. BLS12-381 is currently one of the curves that gather the most interests and yet very few ASIC implementations are optimized for BLS12-381.